THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMPETENCY TOWARDS EMPLOYEE PERFORMANCE WITH MOTIVATION MEDIATION - Noor Hidayat; Hastin Umi Anisah; Hani Muntoha; Tri Ismanto (Jurnal Ilmu Manajemen, 2022)
PP (Government Regulation) No.58 of 2005 concerning regional finance changed to PP No.12 of 2019. This research aims to analyse the influence of competence and organisational culture on employee performance through motivation at Regional Revenue Service Unit. Using a quantitative method, the population is 53 UPPD Banjarmasin 1 employees. Samples were determined using a random sampling technique for 41 UPPD Banjarmasin 1 employees. The research instrument is a questionnaire with a Likert scale—the PLS analysis technique used for data analysis. Research at the UPPD Banjarmasin 1 shows that: (1) organisational culture did not affect employees' performance; (2) competence had an impact on the employees' performance; (3) motivation did not have an impact on the employees' performance; (4) organisational culture affected motivation; (5) competence had an impact on motivation; (6) competence did not affect employee performance through motivation; (7) competence did not have an impact on the employees' performance through motivation. It implies that better organisational culture will have a more substantial impact on the behaviour of the employees and direct results on their motivation.